2014
DOI: 10.1002/cncr.29155
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1, open‐label, dose escalation, safety, and pharmacokinetics study of ME‐344 as a single agent in patients with refractory solid tumors

Abstract: BackgroundThe current phase 1, open-label, dose escalation study was conducted to establish the safety, tolerability, pharmacokinetic profile, and preliminary antitumor activity of the novel mitochondrial inhibitor ME-344 in patients with refractory solid tumors.MethodsPatients with refractory solid tumors were treated in a 3 + 3 dose escalation design. ME-344 was administered via intravenous infusion on days 1, 8, and 15 of the first 28-day cycle and weekly thereafter. Pharmacokinetics was assessed on days 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…In support of our results, another isoflavone glaziovianin A displayed a pattern of differential cytotoxicity in a panel of 39 cancer cell lines that suggested that it induced cell death by inhibiting tubulin polymerization [23]. In addition, it is noteworthy that neuropathy, which is a common toxicity of tubulin inhibitors, was a dose limiting toxicity in the phase I trial of ME-344 [12]. …”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In support of our results, another isoflavone glaziovianin A displayed a pattern of differential cytotoxicity in a panel of 39 cancer cell lines that suggested that it induced cell death by inhibiting tubulin polymerization [23]. In addition, it is noteworthy that neuropathy, which is a common toxicity of tubulin inhibitors, was a dose limiting toxicity in the phase I trial of ME-344 [12]. …”
Section: Discussionsupporting
confidence: 68%
“…In a previous phase I dose escalation clinical trial of ME-344 in patients with solid tumors, a maximal tolerated dose (MTD) of 10 mg/kg was established. Notably, in this clinical trial, a partial response for ≥ 52 weeks was reported in one patient with small cell lung cancer, and four patients had prolonged stable disease [12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For CUDC-907, the compound is readily metabolized and the metabolites have reduced PI3K activity and no HDAC activity (Oki et al 2017). On the other hand, BEZ-235 has a reported C max of 1.4 µM (range 494 nM to 5.7 µM [Bendell et al 2015]).…”
Section: Hierarchical Cluster Analysismentioning
confidence: 99%
“…Gene expression from RNA sequencing data was plotted on the outer ring. IRS2 FGFR3 KDR MAP3K8 KIT PTCH2 FGFR4 MYOD1 HMGA2 MDM2 MYC HRAS SMARCB1 SDHA MCL1 BAP1 RAF1 TP53 ERBB2 DNMT3A NOTCH3 TAZ TSC2 CIC SMO CD276 RARA NF2 CRKL PTPN11 MAPK1 NRAS TBL1XR1 YAP1 EED MSH2 MTOR TMEM127 CREBBP SETD2 BRD4 NOTCH2 CCND2 CCNE1 AURKB CENPF ERBB3 VGLL2 MET BCL11A CACNA1H CDK6 FRS2 EGFR BCOR BCL7A PASK MDM4 PMS1 SOS1 SUFU APC PIK3CA CHD9 DICER1 ATRX KDM5A SYNE1 ATR BRAF FBXW7 TSC1 PTCH1 LIG4 BRCA2 MSH3 HDAC4 ICK RICTOR MALT1 MAML2 FOS CTNNB1 VDAC1 TP53 NRAS PIK3CA BCOR CTNNB1 PTPN11 FGF6 PMS1 KIT EEF1A1 HDAC4 ICK MDM2 PTCH1 CHD2 KDR ZNF350 BCL7A MYC ZNF208 TIM3 FBXW7 SMARCB1 SMO CREBBP YAP1 VGLL2 VDAC1 TSC2 TSC1 TMEM127 TBL1XR1 TAZ SOS1 SHH SDHD RARA RAF1 PTCH2 PDL1 NOTCH2 NF2 MYST3 MYOD1 MYCN MYCL1 MTOR MLL2 MDM4 MCL1 MAPK3K1 IGF2 HMGA2 GATA3 FGF23 FGF14 EEF1A2 EED CTLA4 CRKL CIC CHEK2 CDKN2B CDKN1C CDK6 CDK4 CD68 CCND2 BRD4 ATM BCL11A SUFU MAPK1 FRS2 CDKN2A BAP1 CCNE1 CD276 DNMT3A MALT1 ERBB2 RICTOR NTRK1 MAP3K8 IRS2 LIG4 MET MSH2 PASK HRAS KDM5A ERBB3 FGFR3 MAML2 SDHA DICER1 BRAF CD22 BUB1B CACNA1H ATR CPS1 AURKA LAG3 MUC16 AURKB A2ML1 SYNE1 PKHD1 FOS DCC CHD9 ALK CENPF NOTCH3 BRCA2 APC ATRX FGFR4 MSH3 SETD2 EGFR observed IC 50 values to clinically achievable C max values (Bendell et al 2015;Oki et al 2017). For CUDC-907, the compound is readily metabolized and the metabolites have reduced PI3K activity and no HDAC activity (Oki et al 2017).…”
Section: Hierarchical Cluster Analysismentioning
confidence: 99%